Kloning, Sikuensing dan Analisis Filogenetik Gen Nukleokapsid Protein Virus Tetelo Isolat Bali-1/07 - Ayu Mirah Adi, Anak Agung; Kardena, I Made; Mantik Astawa, Nyoman; Santhia Adhy Putra, Ketut; Hayashi, Yoshihiro; Matsumoto, Yasunobu (Jurnal Veteriner, 2012)
A study was carried out on the molecular characteristics of gene encoding for nucleocapsid protein(NP) of Newcastle disease virus (NDV) Bali-1/07. A portion of the fragment gene was amplified by reversetranscriptase-polymerase chain reaction (RT-PCR). The RT-PCR product purified from the gel was treatedwith Taq polymerase and cloned into plasmid pT7blueT vector. The recombinant plasmid was tranfectedinto Nova blue singles strain of Escherichia coli-competent cells and selected using white and blue colorselection method. Good white colonies were subcultured and tested for presence of expected gene fragmentby polymerase chain reaction (PCR). The correct size PCR product was recloned and sequenced. The PCRproduct of 540 base pairs were sequenced and aligned with several cognates genes of world NDVisolates.using Cluster IW. The phylogenetic analysis was then performed using MEGA 4. Phylogeneticanalysis showed that the NP gene of NDV Bali-1/07 is closely related with virulent NDVs such asGuangxii-11/03, KBNP-4152 and Ast2755/01 with nucleotide sequence homology of 92%, 91.4% and91%respectively, whereas the nucleotide sequence homology with avirulent NDVs such as LaSota and B1were 77%.
Keywords: Cloning, vector, nucleocapsid protein gene, NDV